A Meta-Analysis of 5-Hydroxytryptamine Receptor 1B Polymorphisms With Risk of Major Depressive Disorder and Suicidal Behavior - Yang, Pingliang; Yang, Mengchang; Li, Peng; Cao, Dejun; Gong, Daoyin; Lv, Jiahua; Pu, Linmei; Huang, Sizhou; Liang, Yundan (Frontiers in Psychiatry, 2021)
Purpose: Previous association studies have investigated whether genetic polymorphisms in HTR1B influenced individuals’ susceptibility to major depressive disorder (MDD), anti-depressant response (ADR) and suicidal behavior. However, equivocal evidence was obtained. In this meta-analysis, we aimed to examine the association of HTR1B polymorphisms with risk of MDD, ADR and suicidal behavior. Materials and methods: Studies evaluating the association between HTR1B polymorphisms and risk of MDD, ADR and suicidal behavior were searched in Pubmed, Ovid Medline, web of science and China National Knowledge Infrastructure databases. Summary odds ratios (ORs), 95 % confidence intervals (CIs) and p values were calculated using a fixed or random effects model. Results: Meta-analysis findings revealed a significantly increased risk of MDD with rs6296 GC and GC/CC genotypes (GC vs. GG: OR = 1.26, 95% CI, 1.07-1.48; GC/CC vs. GG: OR = 1.22, 95% CI, 1.04-1.43, respectively). Moreover, rs6298 CT genotype was significantly associated with an increased risk of suicidal behavior (CT vs. CC: OR = 1.48, 95% CI, 1.16-1.88). However, both rs6296 and rs130058 were not significant risk factors for lethal suicidal behavior. Conclusion: This meta-analysis identified that rs6296 and rs6298 in HTR1B may be significantly related to the risk of MDD and lethality of suicide attempts, respectively. Further studies are required to assess the markers in larger cohorts.